Aprendiendo de los urban sketchers. El tiempo en el dibujo. - Ruiz-Padrón, Luis; Gámiz-Gordo, Antonio; Arévalo-Rodríguez, Federico (Universidad de Las Palmas de Gran Canaria, 2014)
After introducing some preliminary ideas about sketching as a method of analyzing architecture and about the architect’s travel sketches, this text reflects on some issues that link the teaching of architectural sketching with the experience of the so called urban sketchers. This organization is dedicated to promoting location drawing all through the world, being faithful to what their members see in their environments. The limited time assigned to each sketch, as well as the recreation of the cityscape and its atmosphere, are issues that can be underlined among others to be learnt from them.
Keywords: Arquitectura - Dibujos y planos; Expresión gráfica arquitectónica